2017
DOI: 10.1371/journal.pone.0182315
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control practice for Crimean-Congo hemorrhagic fever—A multi-center cross-sectional survey in Eurasia

Abstract: BackgroundCrimean Congo Hemorrhagic Fever (CCHF) is a life threatening acute viral infection that presents significant risk of nosocomial transmission to healthcare workers.AimEvaluation of CCHF infection prevention and control (IP&C) practices in healthcare facilities that routinely manage CCHF cases in Eurasia.MethodsA cross-sectional CCHF IP&C survey was designed and distributed to CCHF centers in 10 endemic Eurasian countries in 2016.ResultsTwenty-three responses were received from centers in Turkey, Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 22 publications
(24 reference statements)
0
31
0
Order By: Relevance
“…The healthcare personnel providing care to CCHF patients are at a risk of acquiring the infection [14,15]. The first case of a healthcare worker acquiring CCHF infection was reported in Pakistan in 1976 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The healthcare personnel providing care to CCHF patients are at a risk of acquiring the infection [14,15]. The first case of a healthcare worker acquiring CCHF infection was reported in Pakistan in 1976 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the study in Iran, one of the healthcare workers in the present study, who was anti-CCHV IgG positive, was a laboratory worker. In a 23-centered study investigating the prevention and control [23] of CCHF infection, it was emphasized that all health personnel, including laboratory workers, are at a risk [15]. In a study conducted in Turkey, it was reported that although the nurses had a relatively adequate knowledge of CCHF nosocomial transmission, it is not yet at the level desired [35].…”
Section: Discussionmentioning
confidence: 99%
“…As many nosocomial outbreaks of CCHFV have occurred in endemic areas (Burney, Ghafoor, Saleen, Webb, & Casals, ; Conger et al., ; Naderi, Sheybani, Bojdi, Khosravi, & Mostafavi, ; Pshenichnaya & Nenadskaya, ; Van de Wal, Joubert, van Eeden, & King, ), isolation rooms for CCHF have been established in treatment units throughout Turkey, Iran, Pakistan, Russia, Georgia, Bulgaria, India, Kazakhstan and Kosovo. In addition, adequate training for the use of personal protective equipment and effective waste management and disinfection in the hospital setting have been implemented (Fletcher et al., ). However, as CCHF cases often enter healthcare facilities with non‐specific flu‐like symptoms, late recognition and diagnosis of CCHF cases may hinder the effectiveness of these measures in reducing the occurrence of hospital‐acquired CCHFV infection (Fletcher et al., ).…”
Section: Past: History Of Cchfv Control Measuresmentioning
confidence: 99%
“…In addition, adequate training for the use of personal protective equipment and effective waste management and disinfection in the hospital setting have been implemented (Fletcher et al., ). However, as CCHF cases often enter healthcare facilities with non‐specific flu‐like symptoms, late recognition and diagnosis of CCHF cases may hinder the effectiveness of these measures in reducing the occurrence of hospital‐acquired CCHFV infection (Fletcher et al., ).…”
Section: Past: History Of Cchfv Control Measuresmentioning
confidence: 99%
“…Conversely, grubbing out a habitat and turning it into arable farmland negatively impacts persistence of the pathogen. [54] or transmission through milk, e.g. TBEV [55].…”
Section: Reservoir Host Numbersmentioning
confidence: 99%